A comparison of lexical richness in L2 written productions - Engku Ibrahim, Engku Haliza; Muhamad, Ainon Jariah; Esa, Zaleha (2019)
Research objectives: The objective of this study is to compare the lexical richness of pre-sessional students and that of graduating students (henceforth post-sessional students) of the International Islamic University Malaysia (IIUM).